From Mining to Shop Keeping; the New Way of Life of Gold Miners in Ghana (Journal of Advanced Research in Social Sciences, 2021)
This paper explores how the closure of a century old commercial gold mines has changed the main source of livelihoods and social relations in Obuasi, Ghana. Two years after the mines were closed and almost all workers laid off, there was a paradoxical increase in new luxury residential houses nestling all around the town, and at the same time, there was no certainty in economic stability. Using qualitative research approaches, it was discovered that, the main priority of the laid-off mine workers was to build their own houses as symbol of continuity, the same as they enjoyed when they lived in the company’s housing estates. As much of the severance money was invested into getting private housing, less was left to pursue and sustain economic and livelihood continuity. The study presents a mixture of economic and identity ambiguity amongst the former miners and the town.